2022
DOI: 10.3389/fimmu.2022.1051998
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling tumor microenvironment with natural products to overcome drug resistance

Abstract: With cancer incidence rates continuing to increase and occurrence of resistance in drug treatment, there is a pressing demand to find safer and more effective anticancer strategy for cancer patients. Natural products, have the advantage of low toxicity and multiple action targets, are always used in the treatment of cancer prevention in early stage and cancer supplement in late stage. Tumor microenvironment is necessary for cancer cells to survive and progression, and immune activation is a vital means for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 243 publications
2
28
0
Order By: Relevance
“…Meanwhile, Hanahan (2022) notes that unravelling phenotypic plasticity, non-mutational epigenetic reprogramming, polymorphic microbiomes and senescent cells are likely to be incorporated into the cancer conceptualization of hallmarks. On this basis, the researchers have further revealed that cancer epigenetics, genomic instability and mutations play an important role in the acquisition of cancer hallmarks by cells (Ravi et al, 2022;Zhang et al, 2022).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Hanahan (2022) notes that unravelling phenotypic plasticity, non-mutational epigenetic reprogramming, polymorphic microbiomes and senescent cells are likely to be incorporated into the cancer conceptualization of hallmarks. On this basis, the researchers have further revealed that cancer epigenetics, genomic instability and mutations play an important role in the acquisition of cancer hallmarks by cells (Ravi et al, 2022;Zhang et al, 2022).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…Meanwhile, Hanahan (2022) notes that unravelling phenotypic plasticity, non-mutational epigenetic reprogramming, polymorphic microbiomes and senescent cells are likely to be incorporated into the cancer conceptualization of hallmarks. On this basis, the researchers have further revealed that cancer epigenetics, genomic instability and mutations play an important role in the acquisition of cancer hallmarks by cells (Ravi et al, 2022;Zhang et al, 2022).The emergence of the concept of cancer epigenetics has inspired a wide range of researchers to conduct more in-depth research into cancer mechanisms and cancer treatments. It is generally assumed that epigenetic abnormalities are caused by interactions between multiple protein complexes and their components, such as histone modifications, DNA methylation mechanisms, chromatin remodeling proteins and polycomb (PcG) proteins (Tsai and Baylin, 2011).…”
mentioning
confidence: 99%
“…Immunotherapy leverages immunological principles and methods to activate and enhance the body's immune system. Immunotherapy can enhance the ability of immune system to recognize, attack, and neutralize tumor cells, thereby inhibiting tumor growth (Duan et al, 2019;Zhang et al, 2022). The mechanisms underlying therapeutic vaccines and adoptive cell therapy are shown in Figure 1.…”
Section: Immunotherapy and Cervical Cancermentioning
confidence: 99%
“…In addition, TME is critically involved in clinical intervention and changes treatment outcomes. Modulation of TME is useful for fine-tuning of therapy strategies (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%